Hemiepiphysiodesis for the Correction of Distal Femoral Valgus in Growing Dogs - Vezzoni, Luca; Forzisi, Ida; Ferretti, Antonio; Vezzoni, Aldo (Veterinary and Comparative Orthopaedics and Traumatology, 2021)
Objectives The aim of this study was to describe hemiepiphysiodesis for the treatment of distal femoral valgus in immature dogs and to evaluate its effect on the anatomical lateral distal femoral angle (aLDFA).Methods Skeletally immature dogs with distal femoral valgus deformities that had undergone hemiepiphysiodesis between November 2012 and March 2020 at two private veterinary practices were included. Criteria for inclusion in the study were a preoperative aLDFA below the previously published reference range (94 ± 3.3 degrees) and radiographs of the femur taken preoperatively and at growth plate closure.Results A total of 11 dogs fulfilled the inclusion criteria, and a total of 17 limbs were treated. The mean aLDFA was 82.1 ± 3.2 degrees (range: 76–87 degrees) preoperatively and 93.1 ± 5 degrees (range: 76–99 degrees) at the final re-evaluation. The mean difference between the preoperative and final aLDFA was +11 degrees, which was significant. Undercorrection occurred in 2/17 cases, whereas overcorrection was not recorded. The implants were removed in 12/17 cases, and rebound growth occurred in 3 of these.Clinical Significance Hemiepiphysiodesis for the treatment of distal femoral valgus is a technique that allows for increase in aLDFA and should be considered as an early treatment in affected immature dogs. Monitoring for possible overcorrection using serial radiography is important. Implant removal when the desired aLDFA has been achieved is recommended because the incidence of rebound growth is uncommon in dogs.
Keywords: angular limb deformity; hemiepiphysiodesis; dog; femoral valgus; patellar luxation